Infective endocarditis with spondylodiscitis after prostate biopsy - Pivatto Júnior, Fernando; Stedile, Carolina; Perez, Juliano Adams; Leitão, Cristiane Bauermann (Clinical and Biomedical Research, 2014)
Transrectal ultrasonography-guided prostate needle biopsy is the ideal method to obtain prostate specimens for histological analysis and is therefore frequently used in clinical practice. In the majority of the studies, prostate biopsy is considered a safe procedure with few major complications. In the present report, we describe a case of endocarditis with spondylodiscitis, two very rare complications of prostate biopsy.